First permanent molar mandible root development assesed by periapical radiograph - Nainggolan, Lidya Irani; Munawarah, Adinda (Padjadjaran Journal of Dentistry, 2015)
First permanent molar mandible had already erruptedÂ in Â 6-7Â years oldÂ and theÂ root formation completes atÂ age of 9-10 years. The root formation of first permanent mandibleÂ starts at 5 years and 3 months old, which in radiograph showsÂ asÂ radiopaque area that appearÂ below the crown line, and the root developmentÂ become half of the root formation at 6 years and 2 months old. This stage of first permanent mandible root development can be associated with age estimation. The aim of this study was to determine the stage of the root development, theÂ shape and lenght ofÂ the first permanent molar mandible in children aged 6-10 years old in periapical radiograph. The radiograph was placed on the viewer box and marked the edge of cemento enamel junction and the tip of apex root by pencil and placed the tip of calipper on the two point that have been marked then measured the leght using a ruler. Measurement of the roots length were taken for mesial and distal of each tooth and noted the root shape that assessed form the radiograph. The result of this study shownÂ that the lenght of first permanent mandible of 6-10 years old was in the range of 5,5 -14 mm for mesial root an 4,5 â 12 mm for distal root. The majority of root developmentÂ shape was at stage R Â¾ at 6 years (71,4 %), at 7years (100 %), at 8 years (85,7%) and at the age of 9 years old 85,7% of root shape was at stageÂ Rc and 57,1 % of the rooot shape of the 10 years old was at stage Ac, which stage means the root formation already complete. As a conclusion, the mesial root length appearsÂ longer than the distal length withÂ the rootÂ lenghtÂ variesÂ on the age of 6-10 years old. The root development shape of 6 and 7 until 8 years old mostly shows the root already formed Â¾ of root formation, then at 9 years old the root shape become complete but the apex not yet, and at 10 Â years Â old the stage of the root shape already complete which shown by the closed of the root apex completly.